Μετακίνηση-προσαρμογή 2Δ και 3Δ μη-δομημένων πλεγμάτων με την τεχνική των στρεπτικών ελατηρίων - Αποστόλου, Πέτρος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών. Τομέας Ρευστών. Εργαστήριο Θερμικών Στροβιλομηχανών, 2015)
This diploma thesis, is concerned with an unstructured mesh adaptation method, applied to Computational Fluid Dynamics (CFD) problems with moving boundaries. This method is known in the literature by the term "Unstructured Mesh Adaptation based on the Torsional Spring Analogy". By "adapting" (or "adjusting") is meant the displacement of the internal mesh nodes according to that of boundary nodes. The method takes a prescribed displacement of the boundary nodes (nodes that are located along the contour of the mesh) as input, processes the forces exerted by a system of ctitious springs and, nally, computers the displacement eld of the internal mesh nodes. Through this procedure, the adjustment of the grid is accomplished under the control of the displacement of the nodes lying on the contour. The use of the spring analogy method makes it unnecessary to re-build the com- putational grid for a deformation of the surface of a tested geometry. Conversely, proposes the adjustment of the initial grid to the deformed boundary. Therefore, it is very advantageous in terms of computational time and exible in case of frequent deformations of the mesh. The use of the spring analogy method often refers to applications in CFD, involving geometries with moving boundaries. Some examples are the uid ow around a pi- tching airfoil, the aeroelastic analysis of an aircraft wing, the blood ow in conditions of expansion and contraction of a heart etc. The initial meshes used are unstructured, composed of triangular or quadrilateral elements for 2D and tetrahedral for 3D cases. The quality of the adapted mesh by the spring analogy method certainly depends upon the quality of the initial mesh.Furthermore, the larger the displacement of the boundary nodes, the lower the capacity of the method to tailor the grid by maintaining the capacity of the initial mesh. The method and the programmed software is tested in 2D cases of a) an isolated airfoil and b) a compressor blade rotated by various angles around a point and in 3D cases of the aeroelastic deformation (e.g. torsion and bending) of an aircraft wing. Finally, the limits of the method, for adjusting grids suitable for CFD applications with moving boundaries are discussed.